Extrapolation of experimental data from animals to man. - Krasovskii, G N (1976)
Conditions for extrapolating toxicologic data from animals to man were studied. In the search for general regularities associated with the comparative sensitivity of humans and various species of animals to toxins, it was shown that the toxicity parameters of compounds and the biological constants of mammals correlate with body weight. This relationship is well described by a rectilinear regression equation which holds for more than 100 of the most diverse mammalian biological constants. The toxicity parameters for 80% of the substances also are subordinated to this regularity. This made it possible to develop a computational method for extrapolating toxicologic data from animals to the "average" man. In order to increase the reliability of extrapolation, it is necessary to take into consideration the limits of variability of sensitivity of various population contingents to the effect of chemical compounds, estimate the accuracy of establishing the threshold and no-effect doses of substances under chronic experiment conditions with animals and determine the maximally possible error associated with extrapolating experimental data to the "average" man. In this respect, it is advisable to use a coefficient of reserve whose value should not be less than 10 in order to ensure safe conditions for the transfer of the results of toxicologic studies to public health practice.